Rural investment to accelerate growth and poverty reduction in Kenya - Thurlow, James; Kiringai, Jane; Gautam, Madhur (International Food Policy Research Institute, 2007)
Kenya’s economy is relatively diverse, with both agricultural and industrial potential. However, the economy has performed poorly over the last decade, and poverty and inequality have risen. This paper examines the impact of alternative growth paths and rural investments on poverty using an economy-wide model. It finds that if Kenya continues along its current growth path, its economy will have to grow by more than 10 percent per year over the coming decade to meet the Millennium Development Goal (MDG) of halving poverty by 2015. Therefore, Kenya must search for alternative sources of poverty-reducing growth. The results of the model indicate that poverty is unlikely to decline significantly without an acceleration of agricultural growth. Growth in agriculture is found to benefit both urban and rural households, whereas industry-led growth benefits a smaller segment of the urban population, thus exacerbating inequality. Kenya’s current Economic Recovery Strategy, however, is not optimistic about agriculture’s growth potential, focusing more heavily on industry-led growth. Therefore, as Kenya prepares its new national strategy, the country should place greater emphasis on and direct resources toward accelerating agricultural growth. In assessing the impact of rural investments on growth and poverty, the paper finds that increasing agricultural spending to meet the 10 percent target set by the Maputo Declaration would lift an additional 1.5 million people above the poverty line by 2015. Specific agricultural investments have higher returns in different parts of the country, however. Irrigation favors the lowlands and the poorest segment of the population, while research and extension (R&E) favors the midlands and highlands. Investment in R&E is also found to have the highest returns in both growth and poverty reduction. However, increasing agricultural spending to 10 percent of total spending is insufficient to meet either the MDG or the 6 percent agricultural growth target of the Comprehensive African Agriculture Development Program, which Kenya has recently adopted. . Achieving this target requires nonagricultural investments, such as in roads and market development. Building rural roads and reducing agricultural transaction costs significantly reduces poverty and encourages growth beyond rural areas. While it is necessary to increase spending on agriculture, the fiscal burden of an agricultural strategy can be greatly reduced by improving investment efficiency.